Metformin - Janić, Miodrag (Zdravniški vestnik, 2017)
Metformin represents the first line of treatment and is the most widely prescribed antihypergycemic drug in type 2 diabetic patients. It can be used as monotherapy or in combination with other oral antihyperglycemic drugs or insulin. Additionally, it is also prescribed in type 1 diabetic patients, it proved to be effective in prediabetes and also provided beneficial effects in other insulin resistant states, for example in polycystic ovary syndrome. Nevertheless, the exact molecular mechanism of its action remains unknown. It was shown that it inhibits liver gluconeogenesis, facilitates glucose uptake into peripheral tissues, such as striated muscle; it also acts in the gut. Besides antihyperglycemic effects, metformin was also shown to possess several beneficial, protective effects, so-called pleiotropic effects: particularly on the cardiovascular system and in cancer patients. Metformin has only few side effects, the most serious being metformin-associated lactic acidosis. The latter appears in rare clinical cases with pre-existing chronic kidney disease or advanced heart failure with tissue hypoperfusion, which consequently represent relative contraindications for metformin use. In the past, metformin treatment was usually discontinued when performing iodine contrast imaging, however recently there is evidence of its safety even in patients with higher stages of chronic kidney disease. All in all, metformin is a drug with a long tradition and a promising future.
Keywords: main effects; metformin; osnovni učinki; pleiotropic effects; pleiotropni učinki